Effect of Channa Striatus and Curcuma Longa in Experimentally-Induced Osteoarthritis in Rabbits - Ng, Michelle Yeen Tan (2003)
Channa striatus and Curcuma longa are two well known natural products that have long been used in treating various kinds of ailments. Channa striatus is high in essential amino acids and fatty acids that played an important role in wound healing as well as in anti-nociceptive activities. Curcuma longa on the other hand, contains an active compound called curcuminoids that are responsible for its anti-inflammatory, anti-oxidant and anti-cancer properties. Therefore, in this study, Channa striatus and Curcuma longa extracts were used in the treatment of experimentally induced Osteoarthritis (OA) in rabbits. OA was induced on the right stifle joint of the rabbits in the treatment and the negative control groups by transecting the anterior cruciate ligaments. These animals were left for 8 weeks to develop OA. Radiography and ultrasonography were performed on the induced joints to determine the development of OA prior to Channa striatus and Curcuma Jonga treatments. During the progression of OA, the induced joints began to show sign of OA development as early as the 2nd week after induction of OA as observed in ultrasonograph. Slight joint space narrowing, which reflect the deteriorating articular cartilage was detected by the ultrasonography as early as the 2nd week post induction. On the 3rd week after the induction of OA, ultrasonography was able to detect significant joint space narrowing and total diminution of joint space on the 4th week post induction. In addition to that, irregular joint surface has developed in the induced joints as seen on the ultrasonograph taken on the 5th and the 6th week post induction. Apart from these, other structures such as the infra patellar fat, the patellar ligament and the synovial membrane in the induced joints also underwent osteoarthritic changes as seen in ultrasonographs. On the 8th week post induction there was a significant periarticular soft tissue swelling detected by radiography and ultrasonography. Soft tissue swelling detected on the radiographs was seen as an increased radiopacity area around the joint. In ultrasonographs, the swelling of the joint could be observed as an increased distance between the surface of joint and the skin compared to the normal uninduced joints. On the 9th week of treatment, a significant reduction of soft tissue swelling was observed on Channa striatusand Curcuma longa- treated joints compared to the untreated joints. Although the treatments were effective in reducing inflammations and swelling, these extracts d id not exhibit any improvement on other structures of the joints. Extra bone formation and diminution of the joint space were observed on both radiographs and ultrasonographs on the 9th week of treatment. These similar changes were further confirmed with the gross findings on the opened joints upon euthanasia. In the immunohistochemistry study, synovial membrane biopsies from the normal, treated and negative control joints were obtained to study the general innervation of the synovial membrane. The immunoreactive fibres stained against PGP 9.5, CGRP and NPY antisera were not detected in the control joints compared to the normal synovial membrane. The synovial membrane from the untreated joints was heavily infiltrated with inflammatory cells, which may be account for the diminished immunoreactive nerve fibres from the synovial membrane. However, the number of immunoreactive nerve fibres detected in the synovial membranes from Channa striatus and Curcuma longa treated joints was higher than in the synovial membrane from the control untreated joint. They exhibited a similar distribution to the nerve fib res found in normal synovial membrane but less numerous. Therefore, the present study showed that both Channa striatus and Curcuma tonga extracts showed good signs of healing in OA and these extracts can be used as a good alternative treatment in OA.